(untitled) (Marketing Journal, 2025)
This article analyzes the limitations of existing approaches to evaluating the effectiveness of regional small industrial zones and proposes an integrated system of indicators to address this issue. Based on systematic and comparative analysis methods, № 1 347 the study substantiates the need for a comprehensive approach that incorporates not only economic efficiency but also factors such as management, infrastructure, innovation, and cooperation when assessing the performance of small industrial zones. The rese arch introduces an indicator system that allows for the evaluation of the current status of regional small industrial zones and enables interregional comparison. The findings demonstrate that this approach is of significant importance for improving regiona l industrial policy and making practical decisions regarding the development of small industrial zones.